2013
DOI: 10.1016/j.jval.2013.03.1617
|View full text |Cite
|
Sign up to set email alerts
|

The medical costs and health care utilization for depression treatment by Korean health insurance review & assessment service data

Abstract: When compared to the DD & MHC group, the ASD group was found to be significantly more likely to report issues with availability, obtaining information, and cost of services. CONCLUSIONS: ASD caregivers reported greater difficulty with all five service difficulty measures as compared to caregivers of children with MHC only. However, ASD group reported greater problems only in availability, obtaining information, and cost of services, when compared to DD & MHC group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The latest national epidemiological survey of 6,022 individuals on mental disorder found that the prevalence of depression was the highest among the youngest age group (18–29) compared to older age groups (Cho et al ., ). In contrast, an investigation of Korean national health insurance data on 683,998 patients with depression found that actual treatment contact mainly occurred among the older age group (Kim et al ., ). These two results appear to make sense when they are complement with our finding of a better recognition of depression but with a low rate of treatment initiation among younger patients.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The latest national epidemiological survey of 6,022 individuals on mental disorder found that the prevalence of depression was the highest among the youngest age group (18–29) compared to older age groups (Cho et al ., ). In contrast, an investigation of Korean national health insurance data on 683,998 patients with depression found that actual treatment contact mainly occurred among the older age group (Kim et al ., ). These two results appear to make sense when they are complement with our finding of a better recognition of depression but with a low rate of treatment initiation among younger patients.…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation to harmonize these results is that those with early onset may underestimate their depressive symptoms until they become more impaired (Rhodes et al ., ; Altamura et al ., ) and may seek treatment directly from a psychiatrist, without resorting to other practitioners. This may provide a clue for a question raised by authors (Kim et al ., ) on the inconsistent findings from two major surveys in Korea. The latest national epidemiological survey of 6,022 individuals on mental disorder found that the prevalence of depression was the highest among the youngest age group (18–29) compared to older age groups (Cho et al ., ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In previous studies, factors such as the prejudice or beliefs of patients' family about depression and its treatment, social support, race, and cultural background can influence treatment compliance 31. However, there have been very few studies that have investigated whether there were differences in treatment compliance between Korea and other countries or whether there were factors that could explain such differences 31,32. The Korean Health Insurance Review and Assessment Service reported that antidepressant adherence rate among Korean patients with depression was lower than that in other countries based on the analysis of Korean health insurance data 32.…”
Section: Discussionmentioning
confidence: 99%